Development of a minimum data set for long COVID: a Delphi study protocol - Lisa Lix; Pawan Kumar; Simon Décary; Kiran Pohar Manhas; Andrea Gruneir; Gary Groot; Alison Hoens; Gayle Halas; Angela Cheung; Kieran Quinn; Michelle Kho; Adelaide Amah; et al. (BMJ Open)
Introduction Previous consensus-based long COVID research has focused on establishing research priorities, developing clinical definitions, core outcomes and a list of recommendations of patient-reported outcome measures that can be used to assess and characterise long COVID. Complementing and extending this work, the proposed study will bring together diverse knowledge users to prioritise concepts of care, quality of life and symptoms to inform a national patient registry on long COVID.Methods and analysis We will conduct a Delphi process involving Canadians with lived experiences and/or professional expertise with long COVID (including clinicians, policymakers, caregivers and community leaders). A pool of long COVID survey questions has been established through an environmental scan; these questions were coded by topic and will be presented via a series of online, anonymous survey questionnaires to a diverse cohort of 100 participants. Over the course of three Delphi rounds, participants will prioritise and recommend topics related to care, quality of life and symptoms. We will use the prioritised topics to develop a list of core questions as a minimum data set to standardise data collection and inform a national patient registry on long COVID in Canada.Ethics and dissemination This study has been approved by the University of Saskatchewan Behavioural Research Ethics Board (BEH #4296). Findings will be shared at national conferences and will be published in an open-access peer-reviewed journal. In addition, the minimum data set will be shared with key knowledge users as recommendations to inform a national long COVID patient registry.